2017
DOI: 10.1016/j.appet.2017.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing family meals: Do family structure, gender and employment status influence the odds of having a family meal?

Abstract: Objectives We assessed the odds of having a family dinner by parental gender, family structure and parental employment. Methods This study used data from the American Time Use Survey (ATUS) (2006–2008). Multivariate analyses assessed the odds of two outcomes among parents: 1) eating at all with children and 2) having a family dinner. Results Single men had lower odds of eating at all with children and eating a family dinner in comparison to partnered/married males. Partnered/married women had increased odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…However, contrary to what was hypothesized, the same results were obtained for men. Although, as previously discussed, this result may be associated with Latin American culture [ 95 ], this finding may also reflect men being more actively engaged in family issues, as it has been reported in dual earner-couples in different countries [ 97 , 98 ]. This increases their involvement in the family domain, which in turn may lead to satisfaction with family life, a strong contributor to their overall life satisfaction.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, contrary to what was hypothesized, the same results were obtained for men. Although, as previously discussed, this result may be associated with Latin American culture [ 95 ], this finding may also reflect men being more actively engaged in family issues, as it has been reported in dual earner-couples in different countries [ 97 , 98 ]. This increases their involvement in the family domain, which in turn may lead to satisfaction with family life, a strong contributor to their overall life satisfaction.…”
Section: Discussionmentioning
confidence: 68%
“…Other dyadic studies have reported a similar lack of crossover effects [ 30 ], yet this is an unexpected result in this study, as previous evidence suggests that individuals who share the same environment and experiences (i.e., family members) also share eating habits and satisfaction with food-related life [ 14 , 96 ]. This result may reflect a low frequency of shared meals in dual-earner couples [ 13 , 17 , 97 ], which is associated with time constraints, in particular for full-time employees [ 98 ] and also in dual-earner couples with conflicting work schedules [ 13 ]. Low family meal frequency has been related to unhealthy eating habits [ 13 , 97 ], as well as with lower levels of satisfaction with food-related life [ 14 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no studies have assessed the relationship between these variables while studying different family members simultaneously. In parallel, existing research on food parenting practices and family meals has predominantly focused on mothers [ 17 , 36 , 37 ]. However, fathers also play an important role in their children’s eating habits due to women’s rising participation in the formal labor market.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown associations between availability of nutrient-dense food items (e.g., fruits and vegetables, whole food and fiber products, and reduced/low-fat dairies) at home and youth intake of these foods [7]. Also, when energy-dense, nutrientpoor food items (e.g., high in saturated/trans fat, simple sugars, and sodium-sugar-sweetened beverages, cookies, and packed snacks) have no easy access and are not available at home; there is a decrease in these foods items consumption [8,9].…”
Section: Introductionmentioning
confidence: 99%